School Alienation Among Adolescents in Switzerland and Luxembourg: The Role of Parent and Peer Supportive Attitudes Toward School and Teacher Autonomy Support. Issue 2 (March 2023) - Morinaj, Julia; de Moll, Frederick; Hascher, Tina; Hadjar, Andreas; Grecu, Alyssa; Scharf, Jan
Prior research has shown that socialization agents such as parents, peers, and teachers can play a significant role in adolescents' educational outcomes, both through direct support or indirectly via supportive attitudes that foster students' bonding to school and academic motivation. However, less is known about the effects of parent and peer supportive attitudes and teacher autonomy support on unfavorable educational outcomes such as school alienation. This study investigated the role of socialization agents in the development of school alienation among 544 secondary school students in Switzerland and 535 secondary school students in Luxembourg in grades 7 to 9. Results of structural equation modeling showed that the role of socialization agents varies across the school alienation domains and educational contexts, with peers having the most substantial impact on all three domains of alienation in both countries.